Acute β-N-Methylamino-L-alanine Toxicity in a Mouse Model - Maitham Ahmed Al-Sammak; Douglas G. Rogers; Kyle D. Hoagland (Journal of Toxicology)
The cyanobacterial neurotoxin β-N-methylamino-L-alanine (BMAA) is considered to be an “excitotoxin,” and its suggested mechanism of action is killing neurons. Long-term exposure to L-BMAA is believed to lead to neurodegenerative diseases including Parkinson’s and Alzheimer’s diseases and amyotrophic lateral sclerosis (Lou Gehrig’s disease). Objectives of this study were to determine the presumptive median lethal dose (LD50), the Lowest-Observed-Adverse-Effect Level (LOAEL), and histopathologic lesions caused by the naturally occurring BMAA isomer, L-BMAA, in mice. Seventy NIH Swiss Outbred mice (35 male and 35 female) were used. Treatment group mice were injected intraperitoneally with 0.03, 0.3, 1, 2, and 3 mg/g body weight L-BMAA, respectively, and control mice were sham-injected. The presumptive LD50 of L-BMAA was 3 mg/g BW and the LOAEL was 2 mg/g BW. There were no histopathologic lesions in brain, liver, heart, kidney, lung, or spleen in any of the mice during the 14-day study. L-BMAA was detected in brains and livers in all of treated mice but not in control mice. Males injected with 0.03 mg/g BW, 0.3 mg/g BW, and 3.0 mg/g BW L-BMAA showed consistently higher concentrations (P < 0.01) in brain and liver samples as compared to females in those respective groups.